2011
DOI: 10.1111/j.2041-1294.2011.00066.x
|View full text |Cite
|
Sign up to set email alerts
|

Photoelastic Measurement of High Stress Profiles in Ion‐Exchanged Glass

Abstract: Photoelastic fringes were directly measured to fully characterize high magnitude, steep compressive stress gradients in an ion-exchanged glass, trade named Ion-Armor™. Initially, using a thick (9.9 mm) rectangular bar and circular polariscope arrangement the overall residual stress profile in a bulk specimen was determined. However, due to the relatively large thickness of the specimen, the high density of fringes (steep stress gradient) close to the edge of the specimen became too diffused to allow an accurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…The validity of the measured stress profiles was tested by the criteria of stress equilibrium (difference in the areas of compressive and tensile zones) and by comparison with Na + ion concentration profiles. Our results are compared to analogous studies by Varshneya et al, Jannotti et al and Inaba et al…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…The validity of the measured stress profiles was tested by the criteria of stress equilibrium (difference in the areas of compressive and tensile zones) and by comparison with Na + ion concentration profiles. Our results are compared to analogous studies by Varshneya et al, Jannotti et al and Inaba et al…”
Section: Introductionsupporting
confidence: 73%
“…Figure compares DOL from our measurement (SCALP‐04 and SCALP‐05), Varshneya's DOL values and Na + diffusion depths. Varshneya's DOL values for samples strengthened for 4 and 8 hours were, respectively, 49% and 34% deeper than the SCALP‐04 DOL values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sane and Cooper [16] showed that the stress profile in a sliced sample will show a tension maximum, which was not present in the unsliced plate. Jannotti et al [17] measured the stress profile in a chemically strengthened lithium aluminosilicate glass, but the sample had to be specifically prepared for this purpose. The two opposite surfaces of the glass sample that were perpendicular to the light propagation direction were ground and polished off to remove the layers that could influence the measurement result.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed method of stress profile measurement is demonstrated for a chemically strengthened lithium aluminosilicate (LAS) glass, which is known for its ultra-high surface compression stress (*1000 MPa) and large case depth (up to 1000 lm) [2,17].…”
Section: Introductionmentioning
confidence: 99%